Developing teachers’ competency for inclusive education in Ethiopia - Aschalew T. Kebede; Tlakale N. Phasha (African Journal of Disability)
Background: In light of the increasing diversity within school populations globally, a pressing need arises for nations to prioritise the enhancement of teachers’ competencies in implementing inclusive education, recognising the central role teacher education programmes play in addressing this imperative. Teacher education programmes centred on inclusion not only respond to this global priority but also wield influence on teachers’ attitudes, self-efficacy and stress levels when engaging with diverse learners.